Climatology and ENSO‐related interannual variability of gravity waves in the Southern Hemisphere subtropical stratosphere revealed by high‐resolution AIRS observations. Issue 13 (8th July 2016) - Sato, Kaoru; Tsuchiya, Chikara; Alexander, M. Joan; Hoffmann, Lars
Abstract: A new temperature retrieval from Atmospheric Infrared Sounder with a fine horizontal resolution of 13.5 km was used to examine gravity wave (GW) characteristics in the austral summer at an altitude of 39 km in the subtropical stratosphere over 8 years from 2003/2004 to 2010/2011. Using an S transform method, GW components were extracted, and GW variances, horizontal wave numbers, and their orientations were determined at each grid point and time. Both climatology and interannual variability of the GW variance were large in the subtropical South Pacific. About 70% of the interannual variation in the GW variance there was regressed to El Niño–Southern Oscillation (ENSO) index. The regression coefficient exhibits a geographical distribution similar to that of the precipitation. In contrast, the regression coefficient of the GW variance to the quasi‐biennial oscillation of the equatorial lower stratosphere was not significant in the South Pacific. These results indicate that the interannual variability of GW variance in the South Pacific is controlled largely by the convective activity modulated by the ENSO. An interesting feature is that the GW variance is maximized slightly southward of the precipitation maximum. Possible mechanisms causing the latitudinal difference are (1) dense distribution of islands, which effectively radiate GWs with long vertical wavelengths, to the south of the precipitation maximum; (2) selective excitation of southward propagating GWs in the northward vertical wind shear in the troposphere; and (3) southward refraction of GWs in the latitudinal shear of background zonal wind in the stratosphere. Key Points: Climatology and interannual variability of gravity waves in the middle stratosphere were examined A new temperature retrieval from Atmospheric Infrared Sounder was used Gravity waves are clearly synchronized with ENSO in the South Pacific in austral summer